Hubungan Tingkat Pengetahuan Dismenorea terhadap Perilaku Penanganan Dismenorea pada Mahasiswi Fakultas Kedokteran UNS Surakarta - Sugiantoro, Muhammad Iqbal; Raden, Abkar; Edwin, Erick (Nexus Kedokteran Komunitas, 2012)
Background: Dysmenorrhea occured in 72,4% women where 15,4% of them suffered severe dysmenorrhea that may hinder the person doing activity or work. Behavioral treatment of dysmenorrhea can help the person to reduce the symptoms that may hinder or inhibit a personâs activity. Knowledge is an important determinant for the individual to behave. This study aims to know the relationship between knowledge level of dysmenorrhea to behavioral treatment of dysmenorrhea. Methods: This study was analytical observational with cross sectional approach, and used primary data. These sample were first, second, and third grade students of Medicine Faculty of Sebelas Maret University who suffered dysmenorrhea. Sixty four Samples taken by purpossive random sampling methods. All samples were given questionnaire to measure the knowledge level and behavioral treatment of dysmenorrhea. Data analysis using Chi Square test. Results: The result showed 53% sampleâs kowledge level of dysmenorrhea were good and 47% were less. From behavioral treatment of dysmenorrhea sampleâs ,we get 62% samples treated with his own and 38% went to doctor. From the analysis Chi Square test p= 0,001 and OR= 3,04. Conclusions: Based on result of the study can be concluded that there is a relationship between knowledge level of dysmenorrhea to behavioral treatment of dysmenorrhea. Student with good knowledge level of dysmenorrhea has 3,04 chance to go to the doctor treating dysmenorrhea. Keywords: Knowledge Level of Dysmenorrhea, Behavioral Treatment of Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Â Â Â Â Â Â Dysmenorrhea Â